On institutions that produce and disseminate knowledge - Giorgio Barba Navaretti; Partha Dasgupta; Karl-Göran Mäler; Domenico Siniscalco (Fondazione Eni Enrico Mattei (FEEM), 1997)
This paper investigates institutions for the creation and transmission of knowledge as efficient resource allocation mechanisms. By looking at Science and Technology it develops a two way classification. Science, is a non market allocation mechanism, where knowledge is treated as a pure public good and where the rule of priority provides an incentive scheme for disclosure. Technology, is a market allocation mechanism, where knowledge is treated as a private good and where patents and copyrights preserve property rights. The distinction between these two entities is based on the institutional arrangements involving the allocation of resources for enquiry, not on the differences in the objects and methods of inquiry. The paper compares the rule of priority and patenting as alternative incentive schemes. It also discusses whether it is optimal for society to preserve two different institutions, partly rival and partly complementary, and examines the major policy implications.
Keywords: O31; O34; O32; 330; Science; Technology; Institutions; Incentives; Property rights; Externalities